2020
DOI: 10.1186/s11689-020-09347-w
|View full text |Cite
|
Sign up to set email alerts
|

Risk of neurodevelopmental disorders in children born from different ART treatments: a systematic review and meta-analysis

Abstract: Background Various techniques in assisted reproductive technology (ART) have been developed as solutions for specific infertility problems. It is important to gain consensual conclusions on the actual risks of neurodevelopmental disorders among children who are born from ART. This study aimed to quantify the relative risks of cerebral palsy, intellectual disability, autism spectrum disorder (ASD), and behavioral problems in children from different ART methods by using systematic review and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 54 publications
0
25
0
2
Order By: Relevance
“…We also performed analysis adjusted for birth weight and the similar result was obtained ( online supplemental table S7 ). A systematic review of neurodevelopmental disorders, 5 neuromotor, cognitive, language, and behavioural outcomes of children born after ART showed that ART had no significant effect on children’s neuromotor and cognitive development. 6 A previous study showed no significant difference in the neurodevelopmental scores between children conceived through ART and those conceived naturally; however, it showed a decrease in the score units of each scale among children conceived through ART.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also performed analysis adjusted for birth weight and the similar result was obtained ( online supplemental table S7 ). A systematic review of neurodevelopmental disorders, 5 neuromotor, cognitive, language, and behavioural outcomes of children born after ART showed that ART had no significant effect on children’s neuromotor and cognitive development. 6 A previous study showed no significant difference in the neurodevelopmental scores between children conceived through ART and those conceived naturally; however, it showed a decrease in the score units of each scale among children conceived through ART.…”
Section: Discussionmentioning
confidence: 99%
“… 3 4 Therefore, many studies have investigated the association between ART and neurodevelopmental outcomes. 5–8 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that children born through ICSI have an increased risk of autism and intellectual disability, which may be influenced by paternal characteristics linked to male infertility or the processes of ICSI treatment (4,5,29,30). Kissin et al ( 5) reported a higher incidence of autism in children conceived after ICSI compared with those conceived via conventional IVF in a cohort study of 42,383 children conceived with assisted reproductive technology (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that children born through ICSI have an increased risk of autism and intellectual disability, which may be influenced by paternal characteristics linked to male infertility or the processes of ICSI treatment ( 4 , 5 , 29 , 30 ). Kissin et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation